The region is dead — Long live the region! Remarks on the state of scholarly debate and on the relativity of the term “region” - Wiechmann, Thorsten (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
The inflationary use of the term “region”, observable over the last few years in spatial planning circles, has been accompanied by a new sense of confusion in respect of spatial units. In the absence of convincing definitions of the term “region”, at least of relevance to physical planning, the spatial sciences are called upon to develop a new conception of what is meant by “regions”. The author takes the view that the region should not be (mis)understood simply as a physical section of the earth’s surface, but should rather be viewed as an area characterised by socio-economic integration which defines itself as a loosely connected network through the mutual perception of the actors who operate within it.